RNA binding specificity of hnRNP proteins: a subset bind to the 3' end of introns. - Swanson, M S (1988)
The binding of hnRNP proteins to pre-mRNAs in nuclear extracts, and as isolated proteins, was studied by using monoclonal antibody immunopurification of hnRNP proteins bound to RNase T1-generated fragments. Several major hnRNP proteins, A1, C and D, bind specifically to the 3' end of introns within a region containing the conserved polypyrimidine stretch between the branch site and the 3' splice site. Mutations which alter the conserved 3' splice site dinucleotide AG strongly impair or abolish the binding of the A1 protein as well as of an anti-Sm reactive component(s) to this region. The A1, C and D proteins do not bind efficiently to fragments of either bacterial RNA or the intronless spliced product (mRNA). The binding of these proteins at the 3' end of the intron does not require addition to the extract of exogenous ATP, but remains after ATP addition. These findings demonstrate that several hnRNP proteins have RNA binding specificities on pre-mRNA, and suggest a model for hnRNP particle structure and assembly.